Penggunaan Microsoft Sway untuk Membuat Bahan Ajar Kepengawasan Tentang PKKS dan PKG Tahun 2020 - Mulyana, Anang (Universitas Nusantara PGRI Kediri, 2023)
This paper aims to make it easier for school supervisors and principals to explain PKKS and PKG teaching materials in depth to target schools and to anyone who needs them. This paper is written based on the author's experience in delivering teaching materials to target schools. This paper provides an in-depth explanation of PKKS and PKG, both in writing and via video with the Microsoft Sway link that has been shared. Henceforth supervisors have complete knowledge when implementing PKKS and school principals have a deep understanding of PKG, so it is hoped that quality PKKS and PKG will be able to increase the competency of school principals and teachers and have an impact on achieving graduate competency standards.